The Importance of Morning Exercise Habits for Early Childhood Concentration - Hamidah, Agustin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to explore early childhood teachers’ understanding of the importance of physical activity in supporting young children’s concentration and learning readiness. Employing a qualitative phenomenological approach, the research was conducted from July to September in five kindergartens in Bekasi City, Indonesia. Data were collected through structured interviews with ten kindergarten teachers and direct classroom observations of physical activity practices. The collected data were analyzed using thematic analysis to identify patterns of meaning related to teachers’ understanding, perceptions, and instructional practices. The findings reveal that teachers generally perceive physical activity primarily as a means to support children’s physical health, while its pedagogical role in enhancing concentration and self-regulation is not yet fully understood. Although teachers observed that children tended to be calmer and more focused after engaging in physical activity, such perceptions were not consistently translated into planned and integrated classroom practices. The study also identified a gap between teachers’ conceptual understanding and the actual implementation of regular physical activity, influenced by academic pressures, limited time, and the absence of clear institutional policies. These findings are consistent with previous international studies while highlighting contextual challenges within Indonesian early childhood education. Furthermore, the results demonstrate strong relevance to current national education policies in 2025, particularly the 7 Habits of Great Indonesian Children program, which emphasizes healthy and active lifestyles as a foundation for character development and learning readiness. The study concludes that strengthening teachers’ pedagogical understanding and institutional support is essential for integrating meaningful physical activity into early childhood education practices.